Conformity in Prescription and Administration of Respiratory Distress Protocols in a Tertiary Care Hospital in the Province of Quebec: RELIEVE Study. Issue 1 (January 2020) - Dufort-Rouleau, Camille; Martin, Benjamin; Barré, Vincent; Bédard, Véronique; Rouleau, Émilie Dufort; Beauchesne, Marie-France; Quenneville, Julie; Berteau, Mathieu
Background: Respiratory distress protocols (RDPs) are protocolized prescriptions comprised of 3 medications (a benzodiazepine, an opioid, and an anticholinergic) administered simultaneously as an emergency treatment for respiratory distress in palliative care patients in the province of Quebec, Canada. However, data on appropriate use that justifies the combination of all 3 components is scarce and based on individual pharmacodynamic properties along with expert consensus. Objectives: Our study aimed to evaluate the conformity and the effectiveness of RDPs prescribed and administered to hospitalized adult patients. Methods: This was a prospective and descriptive study conducted in a single center. Prescription and administration conformity were assessed based on predefined appropriateness criteria. Results: A total of 467 adult patients were prescribed a RDP, 175 administrations were documented, and 78 patients received at least 1 RDP. Prescription conformity was assessed on 1473 separate occasions over the trial period. Overall prescription conformity was found to be 37% (95% confidence interval [CI]: 33.6-40.4), and administration conformity was 37.7% (95% CI: 26.2-50.7). Low administration conformity was primarily explained by incorrect indications for RDP use. Seemingly important determinants of higher conformity were prescriber's speciality in palliative care, use of preprinted orders, pharmacist involvement, and hospitalization in the palliative care unit. Conclusion: This study highlights important gaps in the use of RDPs in our institution. Health-care provider training appears necessary in order to ensure adequate conformity and allow for further evaluation of RDP effectiveness.